HOUSEWIVES' PERCEPTIONS TOWARD THE USE OF BLACK SOLDIER FLY TECHNOLOGY IN MANAGING HOUSEHOLD ORGANIC WASTE IN RURAL AREAS - Erpina Santi Meliana Nadeak (International Journal of Social Science, 2023)
Because it produces high-value biomass. However, this technology has not been developed at the community level. Therefore, before black soldier fly technology is promoted to the public, it is important to know the public's perception of the use of this technology. The aim of this research is to analyze housewives' perceptions of the use of black soldier fly technology in processing household organic waste in rural areas, a case study in Laras Dua Village, Simalungun Regency, Indonesia. The sample size was 100 housewives obtained by Slovin equation. The first step, housewives received education and counseling about the use of black soldier flies in processing household organic waste, then continued with interviews using a Likert scale questionnaire. The results of the perception analysis showed that rural housewives strongly agreed that the use of black soldier fly technology provided technological (83.7%), economic (85.7%), and social (82.2%) benefits for rural areas. The positive perception of the technological, economic, and social benefits of using black soldier fly technology will encourage rural communities to use this technology as a sustainable household waste processing solution